2014
DOI: 10.1080/0965254x.2014.914056
|View full text |Cite
|
Sign up to set email alerts
|

How to reduce the negative impact of customer non-compliance: an empirical study

Abstract: This article focuses on the notion of customer non-compliance with front line employees' instructions and company's policies during the service encounter. The aim of the study is to offer an alternative solution to the issue of customer non-compliance, exploring the factors that reduce its negative impact on service quality. For that reason, we developed a conceptual framework integrating the negative influence of customer non-compliance on perceived service quality with three moderating effects. To test the v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 72 publications
0
9
0
Order By: Relevance
“…The participation of the customer in scenarios of creation or involvement, together with the organisations, can define the importance that the consumer brings in the processes of production and development of products or services of the current market [29][30][31][32]. Moreover, Kostopoulos et al [33] indicated that the participation of the client in processes of configuration or development of new products or services implies that the expectations or needs of the client are identified in a more specific way so that in this way, the supplying companies can satisfy the needs demanded from a much more successful production.…”
Section: Consumer As Value Co-creator: Participation Experience Satimentioning
confidence: 99%
“…The participation of the customer in scenarios of creation or involvement, together with the organisations, can define the importance that the consumer brings in the processes of production and development of products or services of the current market [29][30][31][32]. Moreover, Kostopoulos et al [33] indicated that the participation of the client in processes of configuration or development of new products or services implies that the expectations or needs of the client are identified in a more specific way so that in this way, the supplying companies can satisfy the needs demanded from a much more successful production.…”
Section: Consumer As Value Co-creator: Participation Experience Satimentioning
confidence: 99%
“…Typically, customers' response to FLEs' fuzzy requests is either compliance or refusal. Compliance behaviour refers that customers follow FLEs' (or the service provider's) instructions, policies and procedures (Bowman et al, 2004;Kostopoulos et al, 2014). Accordingly, compliance behaviour is defined as overt behavioural adherence to fuzzy requests of FLEs (e.g.…”
Section: Compliance Behaviourmentioning
confidence: 99%
“…As FLEs typically control over the service delivery, fuzzy requests occur as either situational driven options or deliberate plans to improve service capacity. That is, fuzzy requests from FLEs, which might be below the service benchmark, are beneficial to FLEs themselves when customers adapt to and comply with such behaviours in the service process (Fukawa and Erevelles, 2014;Kostopoulos et al, 2014). For example, customers are sometimes requested to share a private service space (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies in relation to the factors that ensure customer compliance have focused on rational decision-making based on cost-benefit analysis (Dellande et al 2004;Lin and Hsieh 2011;Kostopoulos et al 2014). For example, following the rationality-based beliefs model, Li et al (2018) proposed that customer compliance is driven by several factors, including expected technical quality and perceived reasonableness.…”
Section: Introductionmentioning
confidence: 99%